Family Conflict and Harmony of Farmers Family - Dwi Puspita Sari; Herien Puspitawati (Journal of Family Sciences, 2017)
Conflict in the family is one of the caused of family disharmony. The family harmony can be maintained if family functions were implemented in balanced condition. The purposes of the study were identified family conflict of farmer families and family harmony, to identified conflict family and family harmony’s typologies and to analyzed the correlation between characteristics of family and conflict potential with family harmony. The population in this research wasfarmer families in the Sub-district Cipendawa, District Pacet, Cianjur, West Java, with samples as many as 35 familes. Sampling was selected by census then simple random sampling. The results showed that conflicton farmer families was in low level and family harmony was in high level. The typology of family conflict and family harmony was categorized as Type 3 and Type 4. The results also showed that the older mother, tend to lower the conflict within family. However, there was no significant correlation between family conflict with family harmony.